The Investigation Of The Skeletal And Dental Effects Of ACCO Appliance - Ayşenur Ülgen; Ahmet Keleş (Turkish Journal of Orthodontics, 1999)

(untitled)
In this study the effects of modified ACCO appliance was investigated. For this purpose skeletal and dental changes in a group of Class II patients treated with ACCO were compared with the changes in a nontreated control group. The study material consisted of 60 lateral cephalometric films and 30 model photocopies that have been taken before and after molar distalization. For the control group, 40 lateral cephalometric films and 20 model photocopies were taken at the beginning of observation period and 9.6 months after. Two lateral cephalometric films have been taken before and after treatment and control.The treatment group consisted of 15 Class II cases (8 girls and 7 boys). The control group has been consist of 10 Class II cases (3 girls and 7 boys). The mean age at the beginning of the treatment was 13.2 years in the treatment group, and 13.1 years at the beginning of the observation period of the control group. The mean treatment duration of the treatment group was 10.3 months, and the mean observation period of the control group was 9.6 months. The purpose of our study was to distalize the crowns of the first molars by a removable plate, and to upright the roots of the first molars by a cervical headgear of which the outer arms were angulated 25° upward. At the end of the cephalometric investigation showed significant changes in the treatment group. Upper first molars were distalized, and tipped in the mesial direction, and extruded. Upper first premolars were mesialized , and tipped in the mesial direction. Incisors were protruded, and procli-ned. Whereas overjet was increased, overbite was decreased. The angle between the cranial base and the occlusal plane was decreased. The mandibular plane, and the palatal plane rotated downward. When the results of model analysis were measured, significant changes were observed. The distance between upper first molars were increased. The molars were rotated in distopalatal direction.